Feature extraction from CAD model for milling strategy prediction - Balič, Jože (Strojniški vestnik, 2008)
In this paper we present a procedure of feature determination from a CAD model. From the model we extract information, which has the greatest influence on the technological parameters of treatment and then transform this information into appropriate input data for different intelligent processing strategy prediction systems (for example artificial neural network). With formally complex CAD models, different processing strategies are required on a single workpiece. For this reason we use segmentation as described in this paper, to partition the surface of the CAD model into regions, so that we treat each region as an independent model and determine its features.
Keywords: CAD/CAM; frezanje; modeli; segmentacija